WHAT DOES PALLIATIVE CARE MEAN TO YOU? AN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS OF THE UNDERSTANDING, EXPERIENCE AND PERCEPTIONS OF PALLIATIVE CARE IN THE GYNAECOLOGY SETTING. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Stewart, Claire; Archer, Stephanie; Bali, Anish; Hay, Daniel
Abstract : Background: Significant deficiencies in care for patients approaching the end of life have been reported nationwide, particularly for patients managed in the non-specialist settings. Specialist palliative care teams are known to improve patient and family satisfaction but due to limited resources, they cannot care for every patient, and therefore most patients dying in hospitals are under the care of generalist teams, including surgeons and gynaecologists. Gynaecologists may play an important role in 'breaking bad news' and treatment planning for patients with advanced or incurable gynaecological cancer and it is therefore essential that they are competent and confident in the recognition and management of palliative needs. Aims: Previous quantitative research has shown differences in how healthcare professionals understand and perceive palliative care, but they do not help explain why these differences exist. This study therefore aims to bridge this gap by using qualitative methods to obtain rich, detailed data on the understanding, experiences and perceptions of palliative care amongst gynaecology healthcare professionals. Methods: Individual interviews were carried out with 10 healthcare professionals from the gynaecology department of a large tertiary hospital, including consultants, registrars and nursing staff. The data was analysed using Interpretative Phenomenological Analysis to identity relevant themes. Results and Conclusions: Three main themes were identified including Difficult Terminology, Emotional Aspects and "I'm not sure I 'm the right person for the job" These significant human factors must be addressed when planning further education and training in palliative care.